An Analysis of Introductions to Pre-Calculus Books: Perspectives and Intentionality - de Fatima Batistela, Rosemeire [UNESP]; dos Santos, Marli Regina [UNESP] (FapUNIFESP (SciELO), 2024)
In this paper, we turn to the Introductions books of Pre-Calculus books in order to understand what is exposed by their authors when presenting the work to their target audience. Through a phenomenological analysis of the Introductions of these books we seek to highlight the reasons for preparing the work, the objectives that stand out, the contents that the authors consider to be subsidiary to the disciplines of Differential and Integral Calculus, as well as the arguments and teaching concepts explained for them. The analysis highlights the importance of Pre-Calculus in combating failure and dropout in exact science courses and the search for alignment between the mathematics of Basic Education and that necessary for Calculus.
Uma Análise de Introduções de Livros de Pré-Cálculo: Perspectivas e Intencionalidades
Keywords: Book; Calculus; Phenomenology; Pre-Calculus